Price drivers in selected OECD countries: The role of macroeconomic, demographic and institutional factors in a demand-supply model - Stefanos Fotopoulos; Ioannis Kroustalis; Harry Papapanagos; Sofia Delipalla (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
Purpose: This paper aims to investigate the drivers of real house prices in an extended set of selected OECD countries. Design/methodology/approach: The paper uses a data set over the period 2000-2020, employing a panel data analysis based on key macroeconomic, demographic, and institutional factors. The analysis, based on the way demand and supply factors interact in the housing market, sheds light on these factors' simultaneous but opposing effects. Findings: The analysis confirms that high unemployment rates affect house prices adversely, while population growth and raising construction costs push equilibrium prices up. Based on a demand - supply theoretical model, the existence of mortgage interest tax relief regulation is found to be positively associated with equilibrium house prices. Research limitations/implications: While the aim of the paper is to capture as many house price drivers as possible, the list of explanatory variables is not an exhaustive one. Moreover, special conditions in specific countries, such as tax-benefit programs, may need to be examined at an individual country level. Monitoring the trend of the macroeconomic, demographic, and institutional factors, which have been found to affect house prices, could provide an insight for future shifts in house prices. Understanding the way these specific factors affect housing supply and demand could improve government reactions in house price fluctuations. Originality/value: The study enriches the empirical literature on the role of urbanization and deposit rates on house prices, offering, for the first time, alternative explanations of their contribution by analyzing their potentially opposing effects on housing demand and/or supply.
Keywords: C33; C51; R21; R31; 330; Housing; Real house prices; Panel data analysis; Supply-demand channel; Institutional factors; OECD countries